2015
DOI: 10.1038/hdy.2014.127
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of thelytoky in the honey bee Apis mellifera capensis

Abstract: Asexual reproduction via thelytokous parthenogenesis is widespread in the Hymenoptera, but its genetic underpinnings have been described only twice. In the wasp Lysiphlebus fabarum and the Cape honey bee Apis mellifera capensis the origin of thelytoky have each been traced to a single recessive locus. In the Cape honey bee it has been argued that thelytoky (th) controls the thelytoky phenotype and that a deletion of 9 bp in the flanking intron downstream of exon 5 (tae) of the gemini gene switches parthenogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 59 publications
2
21
0
Order By: Relevance
“…We also confirmed that DNA from the fertilized and thelytokous embryos contained the same microsatellite alleles at five unlinked loci, and that there were no more than three alleles at each microsatellite confirming two alleles were derived from the queen and one allele from the sperm from the single drone [ 29 ]. This proves that our colonies had not been invaded by reproductive parasites, as often happens in queenless A. m. capensis colonies [ 51 , 52 ].…”
Section: Methodsmentioning
confidence: 67%
“…We also confirmed that DNA from the fertilized and thelytokous embryos contained the same microsatellite alleles at five unlinked loci, and that there were no more than three alleles at each microsatellite confirming two alleles were derived from the queen and one allele from the sperm from the single drone [ 29 ]. This proves that our colonies had not been invaded by reproductive parasites, as often happens in queenless A. m. capensis colonies [ 51 , 52 ].…”
Section: Methodsmentioning
confidence: 67%
“…The pattern of segregation in such crosses is generally consistent with inheritance of thelytoky being determined by a single recessive locus, which has been termed thelytoky (th) , although more complex modes of inheritance incorporating more loci are also compatible with this inheritance pattern. This putative locus has been mapped to an interval on chromosome 13 [ 18 ] and a 9 bp deletion in this region has been proposed as the causative variant [ 19 ], however, a subsequent study failed to replicate this association [ 20 ] and detected the presence of the deletion in populations of other subspecies where thelytoky is absent (see Materials and Methods for more details).…”
Section: Introductionmentioning
confidence: 99%
“…More recently the transcription factor gemini was suggested to be the controlling gene [36]. But although gemini controls ovary activation and queen pheromone production (Jarosch et al submitted) it does not cause thelytoky [39, Aumer et al submitted]. The simple mode of inheritance based on a single gene with two allelic forms, one for fecundity and one for sterility, in combination with the evolution of social parasitism can be used as an exceptional test system for studying the trade-off between fecundity and longevity by comparing individuals of the same caste with the same physiological constrains: the ones short-lived sterile altruistic workers, the others long-lived highly fecund social parasites.…”
Section: Reproductive Workersmentioning
confidence: 99%